PENGARUH GAYA KEPEMIMPINAN DAN KEPRIBADIAN TERHADAP KINERJA KARYAWAN PADA UMKM TILANYAK JAGOI BABANG, KALIMANTAN BARAT - Jeniper; I Made Sunata; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2023)
UMKM Tilanyak is an oil palm plantation business owned by individuals who have quite a large area of land, besides obtaining their own plantation oil palm crops, they are also collectors of the harvest of the surrounding community who do not yet have a permit to sell to factories. The problems examined in this study are whether leadership style (X1) has a partial effect on employee performance (Y)UMKM Tilanyak, does personality (X2) partially affect employee performance (Y) UMKM Tilanyak, whether leadership style (X1) and personality (X2) simultaneously influences the performance of (Y) UMKM Tilanyak employees, how much influence does leadership style (X1) and personality (X2) have on employee performance (Y) UMKM Tilanyak, which independent variable has the dominant influence on the performance of UMKM Tilanyak employees. The sample used in this study was 60. The research results obtained were leadership style (X1) having a positive and significant effect on employee performance (Y) at Tilanyak Jagoi Babang UMKM, West Kalimantan. Personality (X2) has a positive and significant effect on employee performance (Y) at the Tilanyak Jagoi Babang UMKM, West Kalimantan. Leadership style (X1) and personality (X2) have a positive and significant effect simultaneously on employee performance (Y). The influence of leadership style (X1) and personality (X2) on employee performance (Y) is 30.8%. Personality variable (X2) has a dominant influence on employee performance (Y).